Study of Analytical Controversy of Hermeneutics in the Method of Interpretation of the Qur'an - Istianah; Abdul Matin Bin Salman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The Qur'an is an inexhaustible holy book of Muslims to be studied both in method and content. Along with the advancement of science and technology coupled with the rapid currents of modernism originating from the west, a new method of interpreting the Qur'an was born, known as the hermeneutics method. The purpose of this study is to analyze the hermeneutic controversy in the qur'anic interpretation method. This research uses a qualitative approach and literature review method. Based on the results of research, the hermeneutics method originated from western civilization which in its history was used to interpret the bible. Hermeneutics is paradigmatically divided into theoretical hermeneutics, philosophical hermeneutics and critical hermeneutics. The hermeneutic genre is divided into objectivist, subjectivist and Objectivist–Subjectivist hermeneutics. The attitude of muslim scholars in looking at hermeneutics consists of a accepting cluster, a rejecting cluster and a middle cluster. Islamic thought born from western civilization should be studied critically first, and not immediately adopted without conducting studies first.